MTOR inhibitor use in head and neck squamous cell carcinoma: A meta‐analysis on survival, tumor response, and toxicity. Issue 2 (12th March 2020) - Patel, Jaimin; Nguyen, Shaun A.; Ogretmen, Besim; Gutkind, Jorge S.; Nathan, Cherie‐Ann; Day, Terry
Abstract: Background: Head and neck squamous cell carcinoma (HNSCC) has been rising in incidence primarily related to HPV‐associated oropharyngeal cancers. Novel molecular therapeutics are evolving with the mTOR pathway as a new target. Previous studies have shown variable outcomes with relatively low toxicity. This study reports the tumor response, survivability, and toxicity of mTOR inhibitors (mTORi) in HNSCC. Despite expanding research on this pathway, there remains controversy around mTORi use for treatment of HNSCC. Materials and methods: Studies were included if: (a) Used mTORi alone or in combination with other treatment modalities in HNSCC. (b) Site of cancer included were one of the following: nasopharyngeal, oral cavity, oropharynx, hypopharynx or larynx. (c) All stages of cancer and treatment stage (neoadjuvant, adjuvant, and palliative) were included. The rate of adverse events (AEs), tumor response, progression free survival, and overall survival were meta‐analyzed. Results: From 1299 publications only 11 studies met inclusion criteria with a combined 232 total patients treated. Two studies used mTORi neoadjuvantly, five adjuvantly, and four in palliative/unresectable/metastatic setting. Monotherapeutic mTORi resulted in stabilization of disease (52.5%), but partial response was the most common response when mTORi were combined with chemotherapy and/or radiation (CRT) (48.1%). Survival rate was the highest in the mTORi combined with CRT. Hyperglycemia of any grade was the most commonly reported toxicity while grade 3 or less AEs were the most common grade of toxicity. Conclusion: The use of mTORi as monotherapy in HNSCC has thus far not yielded significant tumor response, however, in combination with other agents, an improved partial tumor response is evident that may or may not be associated with the addition of mTORi. Although adverse events were common, grade 4/5 AEs were uncommon. Further prospective, randomized clinical trials are necessary to confirm the direct roles of these agents in HNSCC tumor response. Level of evidence: 2a